T-box Genes in Early Embryogenesis - Showell, Chris (2004)
The T-box gene family, encoding related DNA-binding transcriptional regulators, plays an essential role in controlling many aspects of embryogenesis in a wide variety of organisms. The T-box genes exhibit diverse patterns of spatial and temporal expression in the developing embryo, and both genetic and molecular embryological studies have demonstrated their importance in regulating cell fate decisions that establish the early body plan, and in later processes underlying organogenesis. Despite these studies, little is known of either the regulation of the T-box genes or the identities of their transcriptional targets. The aim of this review is to examine the diverse yet conserved roles of several T-box genes in regulating early patterning in chordates and to discuss possible mechanisms through which this functional diversity might arise.